1995
DOI: 10.1002/jbm.820290103
|View full text |Cite
|
Sign up to set email alerts
|

Nanoapatite and organoapatite implants in bone: Histology and ultrastructure of the interface

Abstract: This article reports on the reaction of bone to a new family of nanocrystalline hydroxyapatite biomaterials with crystal sizes similar to those of human bone. Pure nanoapatite cylinders and organoapatite cylinders containing a synthetic nanopeptide were analyzed 28 days after implantation into the spongy bone of Chinchilla rabbits. The experimental techniques used for analysis were light microscopy, scanning electron microscopy, and transmission electron microscopy. Both implant types were well incorporated, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 18 publications
4
63
0
4
Order By: Relevance
“…Both implant types were well incorporated and interface events were found to be similar to those observed on human bone surfaces with regard to resorption by osteoclast-like cells and bone formation by osteoblasts. That study revealed a suitability of such materials for both bone replacement and drug release purposes [606]. Similar results were obtained in other studies [607,608].…”
Section: Bone Repairsupporting
confidence: 90%
See 3 more Smart Citations
“…Both implant types were well incorporated and interface events were found to be similar to those observed on human bone surfaces with regard to resorption by osteoclast-like cells and bone formation by osteoblasts. That study revealed a suitability of such materials for both bone replacement and drug release purposes [606]. Similar results were obtained in other studies [607,608].…”
Section: Bone Repairsupporting
confidence: 90%
“…Already in 1990-s, implants prepared from nanodimensional apatites, as well as biocomposites of nanodimensional apatite with organic compounds were tested in vivo [606][607][608]. Cylinders made of both pure nanodimensional apatite and organoapatite containing a synthetic peptide were analyzed 28 days after implantation into spongy bones of Chinchilla rabbits.…”
Section: Bone Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Bioactive materials are classified into surface-active materials and resorbable materials. 2 Surface-active materials bond to bone through an apatite layer formed on the material surface after implantation, [1][2][3][4][5] and it is assumed that the velocity of layer formation correlates with bioactivity. 1,[6][7][8] However, how the formation of the apatite layer affects bioactivity is poorly understood.…”
Section: Introductionmentioning
confidence: 99%